2006
DOI: 10.1007/s10592-006-9118-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical structure and conservation genetics of wild grapevine

Abstract: The distribution of Vitis vinifera subsp. silvestris, the wild grapevine subspecies of Vitis vinifera L., has been dramatically reduced in its major sites of diffusion, at first by the spread, over the last 150 years, of pathogens from North America and, more recently, with fragmentation of habitat and disbranching by humans. In this work, 418 wild grapevine samples, belonging to 78 populations, were collected in their main Mediterranean distribution areas, including the Caucasus area, and the extent of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 20 publications
(20 reference statements)
4
48
1
Order By: Relevance
“…Further information on the genetic background of accessions studied here could be obtained analysing their haplotypes employing cp-SSR markers as previously done by e.g., Grassi et al (2006) or Imazio et al (2006). This data on plastid lineages could provide further insight into the distribution and/ or domestication of V. vinifera ssp.…”
Section: Genetic Variation Through Recombination or Mutation?mentioning
confidence: 80%
“…Further information on the genetic background of accessions studied here could be obtained analysing their haplotypes employing cp-SSR markers as previously done by e.g., Grassi et al (2006) or Imazio et al (2006). This data on plastid lineages could provide further insight into the distribution and/ or domestication of V. vinifera ssp.…”
Section: Genetic Variation Through Recombination or Mutation?mentioning
confidence: 80%
“…Hypervariable chloroplast regions, such as simple sequence repeats (cpSSRs), show higher polymorphism at lower taxonomic levels, but the risk of homoplasy is higher, especially when only length polymorphism is examined. In V. vinifera, cpSSRs are mostly mononucleotide (T or A) repeats that have been extensively used in phylogenetic and phylogeographic studies ArroyoGarcía et al 2006;Grassi et al 2006;Péros et al 2011;Riahi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…All five haplotypes detected by using cpDNA microsatellite markers have been found in the Caucasian ecoregion suggesting that this area is possibly the centre of origin of both wild and cultivated grapevines (Grassi et al, 2006). However, only one provenance from Georgia has been analyzed in this study despite the number of populations of wild grapevine found in Georgia today that display morphological diversity (Ramishvili, 1988).…”
Section: Wwwintechopencommentioning
confidence: 99%